Illustrated key to the genera and catalogue of Mymaridae (Hymenoptera) in the Afrotropical region - Huber, John T.; Read, Jennifer D.; Triapitsyn, Serguei V. (Zootaxa, 2021)
Separate identification keys for females, and for males where known, of the 40 genera of Mymaridae (Hymenoptera: Chalcidoidea) in the Afrotropical region are given. The subgenera of four genera are also included in the key to females. The genera are illustrated with over 300 photographs. The 122 named, valid species reported from the region are catalogued. Reliable host records are reported for 6 genera and 11 species from rearings undertaken in the region. An appendix lists the 27 species from northern Africa and offshore islands (Canary Islands, Madeira) but not recorded in the Afrotropical region as defined in this publication. Camptoptera (Zemicamptoptera) Ogloblin & Annecke, syn. n. is synonymized with Camptoptera (Camptoptera) Foerster. Eofoersteria Mathot, syn. n. is synonymized with Camptoptera Foerster and is treated as subgenus C. (Eofoersteria) Mathot, stat. n.; its type species Eofoersteria camptopteroides Mathot is transferred to Camptoptera as C. (Eofoersteria) camptopteroides (Mathot), comb. n. Polynema megacephala (Risbec) is transferred to Lymaenon as L. megacephala (Risbec), comb. n. Limacis opuntiae Risbec is transferred to Encarsia Foerster (Hymenoptera: Aphelinidae) as E. opuntiae (Risbec), comb. n. A few corrections to Huber et al. (2020) are given.